Final answer:
To combine and simplify the given radical expression 3^√6 × 3^√4, we can use the rule for multiplying exponents and simplify the resulting expression to 2√6.
Step-by-step explanation:
To combine and simplify the radical expression 3√6 × 3√4, we can use the rule for multiplying exponents. When multiplying two exponential terms with the same base, we can add their exponents. In this case, we have 3√6 × 3√4 = 3√(6 × 4) = 3√24.
Since √24 is not a perfect square, we can simplify it further by factoring out any perfect square factors. In this case, √24 = √(4 × 6) = 2√6.
Therefore, the simplified radical expression is 3√6 × 3√4 = 2√6.